2021
DOI: 10.1039/d1nj02163j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of the antiproliferative activity of new heterylmethylidene derivatives of imidazothiazolotriazinones

Abstract: Two series of regioisomeric heterylmethylidene derivatives of imidazo[4,5-e]thiazolo[3,2-b]-1,2,4-triazines and imidazo[4,5-e]thiazolo[2,3-c]-1,2,4-triazines were synthesized. Several compounds exhibiting high antiproliferative activity were found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…In the 1 H NMR spectra of products 1a–w and 5a–z , a strong downfield shift of the indole H-4′ proton signals (8.79–8.89 and 8.26–8.86 ppm, respectively) was observed, which is characteristic of proximity of the carbonyl group C(7)O or C(8)O. 5,6 The homogeneity of compounds 1f–h , 1j , 1k , 1n , 1p , 1r , 1u–w and 5b , 5e , 5f , 5h , 5k , 5p , 5r , 5x–z was confirmed by powder X-ray diffraction. The results of the analysis of the experimental powder diffraction patterns of the compounds 1f–h , 1j , 1k , 1n , 1p , 1r , 1u–w and 5b , 5e , 5f , 5h , 5k , 5p , 5r , 5x–z showed that the investigated samples were single-phase.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…In the 1 H NMR spectra of products 1a–w and 5a–z , a strong downfield shift of the indole H-4′ proton signals (8.79–8.89 and 8.26–8.86 ppm, respectively) was observed, which is characteristic of proximity of the carbonyl group C(7)O or C(8)O. 5,6 The homogeneity of compounds 1f–h , 1j , 1k , 1n , 1p , 1r , 1u–w and 5b , 5e , 5f , 5h , 5k , 5p , 5r , 5x–z was confirmed by powder X-ray diffraction. The results of the analysis of the experimental powder diffraction patterns of the compounds 1f–h , 1j , 1k , 1n , 1p , 1r , 1u–w and 5b , 5e , 5f , 5h , 5k , 5p , 5r , 5x–z showed that the investigated samples were single-phase.…”
Section: Resultsmentioning
confidence: 97%
“…Oxindolylidene derivatives of imidazothiazolotriazines were synthesized according to earlier 5 b elaborated methods via condensation of imidazothiazolotriazine hydrobromides with isatin or N -alkylisatins prepared by alkylation of unsubstituted isatin with the corresponding alkylhalogenides. The linear structures 1a–w were formed in boiling methanol in the presence of 1.07 equiv.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations